Determinants of the Effectiveness of Receivables Control at CV. Lima Daun Semanggi - Wijayanti, Yunisa Meiliana; Wijayanti, Anita; Dewi, Riana Rachmawati (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
This research was conducted to test and analyze the influence of sales accounting information systems and internal control on the effectiveness of control of receivables at CV. Lima Daun Semanggi. This type of research is quantitative research. The population used in this research were employees from CV. Lima Daun Semanggi. The sampling technique used in this research was the purposive sampling method by distributing questionnaires to 34 respondents. The data analysis method used in this research is multiple linear regression analysis which was processed using the SPSS version 26 program. The results of the research show that the sales accounting information system partially has no effect on the effectiveness of receivables control, while internal control partially has an effect on the effectiveness of receivables control.